Critical cause analysis and sustainable solutions for urban flood control: a practical case from the Tejipió river basin - Silva, Gabriele Joana de Souza Feliciano da; Dantas , Pedro Henrique; Moura, Micaella Raíssa Falcão de (Technical and Scientific Journal Green Cities, 2025)
This study is a critical analysis of possible urban flooding regions in the Tejipió River basin, located in the state of Pernambuco. To carry out the research, the factors of land use and occupation, slope, hypsometry and water bodies that may contribute to the occurrence of these floods were investigated. And mitigating measures adopted/proposed by the municipal government. This is a case study, with the objective of exploratory and qualitative research, using bibliographic sources. In this sense, guidelines were given on the problem and the application of the QGIS 3.10.9 software, as a tool for performing map analysis on flood factors. And through the data, the application of sustainable solutions, such as NBS (Nature-Based Solutions), permeable pavements and green infrastructure, as agents to reduce these events, was observed. In conclusion, theoretical constructions and recommendations on the subject, and the relationship between river preservation and the use of sustainable measures, are strategic tools to guarantee effective solutions and ensure the safety of affected communities and the conservation of water resources.